Critical Analysis of Blue Ocean Principles to Maximize the Business Opportunity and Minimize the Risk for the Success of Uber E- Taxi - Rani, Dr.K.Jawahar; Lekshmi, Dr. R.S; Jenifer, A. Priya; V.Santhya (The journal of contemporary issues in business and government, 2021)
A strong framework for seeking potential business opportunities is the Blue Ocean Strategy. This paper explains the concepts of the blue ocean strategy, principle and risk associated with Uber and how Uber breaks down conventional strategic competitive thinking and uses strategic concepts of the blue ocean to increase demand and benefit for the company. The four principles are how to establish uncontested market space by restoring market boundaries, concentrating on the big picture, reaching new market spaces beyond current demand and supply, and having the strategic sequence right. Uber discovered the untapped e-taxi market, which had enough opportunities for rapid growth and profitability, and this initiative made it possible for them to identify their larger, deeper potential e-taxi market in its strategic formulation, which was not explored.